A finite point method for compressible flow - Löhner, Rainald; Sacco, Carlos; Oñate, Eugenio; Idelsohn, Sergio (International journal for numerical methods in engineering, 2002)
A weighted least squares finite point method for compressible flow is formulated. Starting from a global cloud of points, local clouds are constructed using a Delaunay technique with a series of tests for the quality of the resulting approximations. The approximation factors for the gradient and the Laplacian of the resulting local clouds are used to derive an edge‐based solver that works with approximate Riemann solvers. The results obtained show accuracy comparable to equivalent mesh‐based finite volume or finite element techniques, making the present finite point method competitive. Copyright © 2001 John Wiley & Sons, Ltd.